Pentingnya Pendidikan Teknologi untuk Generasi Alpha - Indriyani; Kurnia Wulandari; Salsabila Az-Zahra; Dian Puspita (Jurnal Pustaka Cendekia Pendidikan, 2025)
Generation Alpha, born in 2010 and onwards, is the first generation to fully grow up in a digitally connected world. They are highly exposed to technology, from smart devices to social media, which have become an inseparable part of their lives. However, although technology offers various benefits such as faster access to information and opportunities for creativity, major challenges also arise, such as the risk of dependence on technology, decreased social skills, and exposure to unverified information. Therefore, technology education is a very important element in preparing Generation Alpha to face the challenges of the 21st century. This article aims to analyze the role of technology education in shaping the character and skills needed by Generation Alpha. The main focus of this discussion is on digital literacy, where children are not only taught how to use technology, but also invited to understand basic concepts such as digital ethics, privacy, and critical information management. In addition, this article also explores how technology education can contribute to character building, such as increasing creativity, problem solving, cooperation, and social responsibility. Through a literature review referring to previous research, this article highlights the importance of collaboration between parents, teachers, and the community in assisting children in managing the use of technology. Technology-based education must ensure that children not only master digital tools and devices, but also have strong social and emotional skills to be able to interact with the world positively. Thus, the right technology education will prepare Generation Alpha to become creative, critical, and adaptive individuals to changes that occur in global society.